NEUROPHYSYOLOGY MEMORY - Sri Kusrohmaniah (Buletin Psikologi, 2008)
This paper describes neuropsychology bases of human memory. First, the author presents definitions of memory according to biopsycholo‐gical point of view. Next, the human nervous system and how neurons work are explained. Finally, the paper explicates the major parts of human brain and their roles in memory.